Ice core reconstruction of sea ice change in the Amundsen‐Ross Seas since 1702 A.D. - Elizabeth R. Thomas; Nerilie J. Abram (Geophysical Research Letters)
Abstract Antarctic sea ice has been increasing in recent decades, but with strong regional differences in the expression of sea ice change. Declining sea ice in the Bellingshausen Sea since 1979 (the satellite era) has been linked to the observed warming on the Antarctic Peninsula, while the Ross Sea sector has seen a marked increase in sea ice during this period. Here we present a 308 year record of methansulphonic acid from coastal West Antarctica, representing sea ice conditions in the Amundsen‐Ross Sea. We demonstrate that the recent increase in sea ice in this region is part of a longer trend, with an estimated ~1° northward expansion in winter sea ice extent (SIE) during the twentieth century and a total expansion of ~1.3° since 1702. The greatest reconstructed SIE occurred during the mid‐1990s, with five of the past 30 years considered exceptional in the context of the past three centuries.